The Management of Intraabdominal Testis: A Survey of the World Federation of Associations of Pediatric Surgeons (WOFAPS) Practices - Shehata, Sameh; Hadziselimovic, Faruk; Khater, Doaa; Kotb, Mostafa (Frontiers in Pediatrics, 2022)
BACKGROUND AND OBJECTIVE The optimal treatment protocol of intraabdominal testis is still a matter of debate and until now there are a lot of areas of controversy as regards this challenging subtype. The aim of this report is to document current practice patterns among surgeons from different continents through an online Redcap survey supervised the World Federation of the Association of Pediatric Surgeons (WOFAPS). METHODS A 16-question-survey related to the management of intraabdominal testis was created and administered via RedCap. The WOFAPS headquarters sent an email to all members inviting voluntary survey participation. Data were entered using Microsoft EXCEL spreadsheet and analyzed. Descriptive statistics were performed for each survey item. RESULTS There were 436 WOFAPS members who participated in this study with a response rate of 29%, and the vast majority were pediatric surgeons. Only 13% tried to use hormone therapy aiming to induce testicular descent or to improve future fertility. The choices of various surgical techniques were noted. During laparoscopy, if vessels and cord structure were seen entering the ipsilateral internal inguinal ring, most respondents chose to explore the groin. On the other hand, should there was an absent or atrophic testis, the respondents were split on whether to perform a contralateral orchiopexy. CONCLUSION: This survey describes the current practices of a sample of pediatric surgeons and urologists in the management of intraabdominal testis. The use of hormonal treatment, timing of fixation and management in case of passing through vas and vessels through DIR were undisputable. However, management of low-lying and peeing testis together with the management of contralateral testis were still debatable.